English Teachers’ Technology Integration in Classroom Through the SAMR Model - Nur Aini; Perangin Angin, Odriani Musdalifa; Bulan Rahma Alya; Izza Raihana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
As technology continues to evolve and become increasingly prevalent in English language classrooms, teachers must integrate it systematically to ensure that it effectively enhances students’ learning experiences. Currently, the use of digital media in English language teaching remains inconsistent, with technology often functioning only as a replacement for conventional tools. This study investigated the types of digital media used by English teachers at SMAN 7 Medan and analyzed the extent to which technology integration reflects the SAMR model (Substitution, Augmentation, Modification, and Redefinition). Using a qualitative approach, data were collected through structured interviews and analyzed thematically. The findings showed that teachers commonly used PowerPoint, projectors, educational videos, TikTok, and voice recordings in their instruction. Most practices remained at the Substitution and Augmentation levels, while only limited activities reached the Modification level through more interactive and creative learning tasks. The Redefinition level was minimally achieved. These findings indicate that technology integration in English language teaching is still in a transitional stage and highlight the importance of continuous professional development to support more innovative and transformative teaching practices.